Estudio de alteraciones neurocognitivas en pacientes infectados por el virus de la inmunodeficiencia humana (2019)
Introduction: The Human Immunodeficiency Virus, known for its impact on the immune system, causes progressive neurologic manifestations with cognitive impairment, disrupting attention functions, memory, language, execution and processing of information. The latter negatively interferes in social, work and family life of the patient. Objectives: To evaluate alterations in varied neurocognitive functions on patients with Human Immunodeficiency Virusinfection, at a health institution in Ibague, Colombia. Method: The Montreal Cognitive Assessment (MoCA) was used. It was designed as a tool to determine mild cognitive alterations. The study population was made up of 44 carriers of Human Immunodeficiency Virus who were selected within a framework of non-probabilistic sampling and with purposive sample or convenience, between 14 and 75 years old. Results: Greater neurocognitive impairment in patients diagnosed with Human Immunodeficiency Virus in legal age; some epidemiological data indicate that the older age is associated with a higher prevalence of neurocognitive disorder associated with Human Immunodeficiency Virus. Conclusions: The study of the neurocognitive impairment mechanisms in patients with Human Immunodeficiency Virus becomes increasingly more relevant, as their life expectancy increases daily. On the other hand, it causes complications with greater prevalence of medical psychiatric and neurological comorbidity. © 2019 Academia Nacional de Medicina. All rights reserved.